Pengaruh Penambahan Ammonium Sulfat Terhadap Kadar Serat dan Ketebalan pada Nata de Soya dari Limbah Cair Tahu - Ismawanti Ismawanti; Maswati Baharuddin; Wahyu Rizandi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
The research aimed to know the production of cellulose in tofu liquid waste, the effect of adding ammonium sulfate to the nata de soya, and the quality nata de soya produced from Tofu Liquid Waste. The parameters used are the determination of the thickness and weight, measure of water, and fiber test of nata de soya. By using variations of the addition of ammonium sulfate 10 g, 15 g, 20 g, and 25 g. 35 grams of sugar in 500 mL of tofu liquid waste, starter bacteria Acetobacter xylinum as much 100 mL, and fermented for 14 days at a temperature of 28-30oC. The quality nata de soya highest of the addition 15 grams of ammonium sulfate with a thickness of 1.7 cm, weight 231.0 grams, the lowest water content of 94.23% and the highest fiber content of 2.41%.